2018
DOI: 10.3389/fmars.2018.00117
|View full text |Cite
|
Sign up to set email alerts
|

Biogeochemical Regeneration of a Nodule Mining Disturbance Site: Trace Metals, DOC and Amino Acids in Deep-Sea Sediments and Pore Waters

Abstract: Increasing interest in deep-sea mineral resources, such as polymetallic nodules, calls for environmental research about possible impacts of mineral exploitation on the deep-sea ecosystem. So far, little geochemical comparisons of deep-sea sediments before and after mining induced disturbances have been made, and thus long-term environmental effects of deep-sea mining are unknown. Here we present geochemical data from sediment cores from an experimental disturbance area at 4,100 m water depth in the Peru Basin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 64 publications
5
53
0
Order By: Relevance
“…observation is in agreement with a recent EBS disturbance experiment, which has been conducted in the DISCOL area in (Greinert, 2015). The freshly created EBS track in the DISCOL area was re-visited weeks after the disturbance experiment, where the surface sediment was mostly removed and deeper sediment layers were exposed without visible sediment mixing (Boetius, 2015;Paul et al, 2018). In a study on the geochemical regeneration in disturbed sediments of the DISCOL area in the Peru Basin, Paul et al (2018) have shown that the bulk Mn-rich top sediment layer, which has been observed in undisturbed sediments, is removed in the 5-week old EBS disturbance track.…”
Section: Depths Of Small-scale Disturbance Experimentsmentioning
confidence: 99%
“…observation is in agreement with a recent EBS disturbance experiment, which has been conducted in the DISCOL area in (Greinert, 2015). The freshly created EBS track in the DISCOL area was re-visited weeks after the disturbance experiment, where the surface sediment was mostly removed and deeper sediment layers were exposed without visible sediment mixing (Boetius, 2015;Paul et al, 2018). In a study on the geochemical regeneration in disturbed sediments of the DISCOL area in the Peru Basin, Paul et al (2018) have shown that the bulk Mn-rich top sediment layer, which has been observed in undisturbed sediments, is removed in the 5-week old EBS disturbance track.…”
Section: Depths Of Small-scale Disturbance Experimentsmentioning
confidence: 99%
“…Sediment grain size analysis was done by laser diffraction with a Malvern Mastersizer 2000 particle analyzer (Malvern Instruments, UK) and sediment fractions were classified according to Wentworth (1922 (2002). Pore water metal content was not measured in this study but has been assessed for the experimental area by Paul et al (2018)…”
Section: Sediment Characteristics and Metal Contentsmentioning
confidence: 99%
“…Therefore, most metals are bound to the solid phase of the sediment and are not bioavailable, which most likely explains our findings of similar copper burdens in the nematodes from the control and the Burial treatments. A recent study investigated the long-term and short-term effects of sediment disturbance on metal and trace element concentrations in the solid phase of the sediment and the pore water (Paul et al, 2018). The authors found that while some solid phase elements still deviated from predisturbance levels even after 26 years, levels of trace metals in the pore water levels returned to pre-disturbance values in a short time frame of several weeks.…”
Section: Increased Copper Concentrations In the Added Substrate Are Nmentioning
confidence: 99%
See 2 more Smart Citations